From experience to expectation. The history of the concepts of Reinhart Koselleck - Fernández Riquelme, Sergio (2018)
The world is transformed at breakneck speed into the era of globalization. The historian Reinhart Koselleck illuminated the genesis of this transforming globalized reality (Modernity), and provided a historiographical model, on political-social concepts, still in force to understand the new society that shone (Gesellschaft) in his words and speeches. His History of Concepts appears as a theoretical instrument of the first level to reconstruct our contemporary human action (SattelZeit), in each moment and place, from the interrelation between experience and expectation, of our “future past”.